Livid [compact disc, unabridged] - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series, 2022)
Forensic pathologist Kay Scarpetta has just inherited one of the most notorious cases of her career. Two years ago, a former beauty queen's body washed up on the shore of Wallops Island, Virginia. She was last seen on a boat with her fiancé, who has since been held in jail while awaiting trial. Scarpetta must act as the expert witness for the case, an investigation previously botched by another forensic pathologist. After a grueling cross-examination by the prosecutor, Scarpetta leaves the court only to discover that the sister of the judge on her case has been found dead. Scarpetta ultimately finds herself facing a powerful, invisible enemy who's planning the unthinkable.